DANGER Signals Activate G-Protein Receptor Kinases Suppressing Neutrophil Function and Predisposing to Infection After Tissue Trauma - Kim, Hyo In; Park, Jinbong; Gallo, David; Shankar, Sidharth; Konecna, Barbora; Han, Yohan; Banner-Goodspeed, Valerie; Capers, Krystal R; Ko, Seong-Gyu; Otterbein, Leo E; Itagaki, Kiyoshi; Hauser, Carl J (Annals of surgery, 2023)
Surgery injures tissue and predisposes to local and systemic infections. We studied injury-induced immune dysfunction seeking novel means to reverse such predisposition. Injury mobilizes primitive 'DANGER signals' (DAMPs) activating innate immunocyte (neutrophils, PMN) signaling and function. Mitochondrial (mt) formyl peptides (FP) activate G-protein coupled receptors (GPCR) like FPR1. mtDNA and heme activate toll-like receptors (TLR9, TLR2/4). GPCR kinases (GRKs) can regulate GPCR activation. We studied human and mouse PMN signaling elicited by mtDAMPs (GPCR surface expression; protein phosphorylation or acetylation; Ca2+ flux) and antimicrobial functions (cytoskeletal reorganization, chemotaxis (CTX), phagocytosis, bacterial killing) in cellular systems and clinical injury samples. Predicted rescue therapies were assessed in cell systems and mouse injury-dependent pneumonia models. mtFPs activate GRK2, internalizing GPCRs and suppressing CTX. mtDNA suppresses CTX, phagocytosis and killing via TLR9 through a novel, non-canonical mechanism that lacks GPCR endocytosis. Heme also activates GRK2. GRK2 inhibitors like paroxetine restore functions. GRK2 activation via TLR9 prevented actin reorganization, implicating histone deacetylases (HDACs). Actin polymerization, CTX, bacterial phagocytosis and killing were also rescued therefore by the HDAC inhibitor valproate. Trauma repository PMN showed GRK2 activation and cortactin deacetylation which varied with severity and was most marked in patients developing infections. Either GRK2 or HDAC inhibition prevented loss of mouse lung bacterial clearance, but only the combination rescued clearance when given post-injury. Tissue injury-derived DAMPs suppress antimicrobial immunity via canonical GRK2 activation and a novel TLR-activated GRK2 pathway impairing cytoskeletal organization. Simultaneous GRK2/HDAC inhibition rescues susceptibility to infection after tissue injury.